Kajian Kehadiran Inang Primer pada Pertumbuhan Semai Cendana - Wawo, Albertus Husein (Universitas Atma Jaya Yogyakarta, 2004)
Sandalwood (Santalum album L.) is known as a fancy plant. Since they have high economic value, it often over exploited. As a consequence, the population dramatically decreased in their habitats. Some efforts have been done to conserve this plant in order to prevent their extinction, i.e. seedling multiplication. As a hemiparasitic plant, sandalwoods need other plants for a host which grow around. Therefore, determining of the the primary host is a necessary aspect in multiplication of sandalwood seedling. This study used three species plants to serve sandalwood seedling as primary host in pot cultures consist of local leucaena (Leucaena glauca), vilosa (Acacia villosa) and calliandra (Calliandra calothyrsus). The results of this study indicated that A. vilosa is better for a primary host than L. glauca and C. calothyrsus as well. Number of root connection between sandalwood seedlings and their hosts have a close correlationship to the leaf number and the sandalwood seedling dry weight, whereas no significant correlationshifp to their height.